Analisis Yuridis Perbedaan Akta Otentik dan Akta di Bawah Tangan Perspektif Asas Kebebasan Berkontrak - Susi Susanti; Adnan Adnan; Andriadin Andriadin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This journal examines the comparative legal strength between authentic deeds and private deeds in the context of civil disputes. Authentic deeds, which are executed before a competent public official, possess full and binding evidentiary strength, unless proven otherwise. In contrast, private deeds only hold evidentiary value if their content and signatures are not disputed by the concerned parties. This. This research uses a normative juridical method with a legislative approach, a comparative approach, and a conceptual approach. The research shows that although Article 1338 paragraph (1) of the Civil Code sets the principle of freedom of contract, allowing parties to choose between written or oral forms and authentic or private deeds, this freedom is not absolute. Research shows that in civil cases, authentic deeds have a stronger legal standing compared to private deeds, especially in terms of their evidential strength.